2020
DOI: 10.1371/journal.pone.0240332
|View full text |Cite
|
Sign up to set email alerts
|

Modulating electrospun polycaprolactone scaffold morphology and composition to alter endothelial cell proliferation and angiogenic gene response

Abstract: The aim of this study was to look at how the composition and morphology of polymer scaffolds could be altered to create an optimized environment for endothelial cells. Four polycaprolactone (PCL) scaffolds were electrospun with increasing fibre diameters ranging from 1.64 μm to 4.83 μm. The scaffolds were seeded with human umbilical vein endothelial cells (HUVEC) and cultured for 12 days. PCL scaffolds were then electrospun incorporating decellularized bovine aorta ECM and cultured in a hypoxic environment. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 68 publications
2
18
1
Order By: Relevance
“…2). This consistency enables us to eliminate the size effect on cell behaviour [43][44][45] and thus ascribe the results in part to the laminin. The range between three groups was able to be tailored with the maximum variation of 1 lm.…”
Section: Discussionmentioning
confidence: 86%
“…2). This consistency enables us to eliminate the size effect on cell behaviour [43][44][45] and thus ascribe the results in part to the laminin. The range between three groups was able to be tailored with the maximum variation of 1 lm.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies on similar electrospun fibres have shown that different cell types can respond in a comparable manner, and co-culture can initiate other functions. 37,56,86,87 As the liver is a complex organ, a layer of liver tissue is usually composed of hepatocytes, epithelial cells, Kupffer cells, stellate cells, and liver sinusoidal endothelial cells. How to design or to use a potential scaffold depends on what function is required.…”
Section: Discussionmentioning
confidence: 99%
“…This process begins by dissolving the polymer in an organic solvent. Common solvents used include hexafluoroisoproponol, chloroform, mixtures of chloroform and methanol, , and acetone . The type of solvent used has little impact on bulk or surface properties after fabrication, but solvent choice does impact the solubility of blending polymers, cytotoxicity to tissue constructs, and ease of use.…”
Section: Biofabrication Methods For Pcl Scaffoldsmentioning
confidence: 99%